An aeroelastic model for vortex-induced vibrating cylinders subject to frequency lock-in. (February 2016) - Besem, Fanny M.; Thomas, Jeffrey P.; Kielb, Robert E.; Dowell, Earl H.
Abstract: This work presents a novel way to calculate the response amplitude of an elastically supported cylinder experiencing vortex-induced vibrations. The method couples a computational fluid dynamic (CFD) model of the shedding vortex flow to a structural model representation of the elastically supported cylinder. The aerodynamic forces on the cylinder are calculated using a harmonic balance, frequency domain solver. Three cases are considered: the cylinder vibrating transverse to the flow, in-line with the flow, and with both degrees of freedom. Two shedding patterns are observed, symmetric and antisymmetric, depending on the lock-in region considered. The in-line degree of freedom does not have a significant effect on the cylinder cross-flow response, except for very low mass or very low damping. Abstract : Highlights: We characterized the shedding patterns for transverse and in-line lock-in regions. We used a fluid-structure interaction model with a frequency domain CFD code. The transverse lock-in region is more accurately captured and matches experiments. The in-line amplitude is insignificant except at very low mass and damping. For very low mass ratios, it is necessary to model both degrees of freedom.